GROUND OF PHARMACOKINETIC INDICES OF MEDICINAL FILMS FOR TASKS OF MATHEMATICAL DESIGN - Tymchenko І. М.; Davtian, L. L.; Vlasenko І. О.; Yeroshenko, S. S.; Babintseva, L. Yu. (Medical Informatics and Engineering, 2012)
The search of indices is conducted for creation of model at the pharmacokinetic study of medicinal means. By methods of in vivo with the use of a single-chamber model, pharmacokinetic research has been carried out of the medicinal films containing metronidazole. It has been established, that films have a local effect because at the moment the flow of extrication of the substances from the films is greater than a penetration flow through natural biological barriers of an organism.